Gut Microbiota Composition in Prediabetes and Newly Diagnosed Type 2 Diabetes: A Systematic Review of Observational Studies - Letchumanan, Geetha; Abdullah, Natasya; Marlini, Muhamad; Baharom, Nizam; Lawley, Blair; Omar, Mohd Rahman; Mohideen, Fathima Begum Syed; Addnan, Faizul Helmi; Nur Fariha, Mohd Manzor; Ismail, Zarini; Pathmanathan, Siva Gowri (Frontiers in Cellular and Infection Microbiology, 2022)
Evidence of gut microbiota involvement in regulating glucose metabolism and type 2 diabetes mellitus (T2DM) progression is accumulating. The understanding of microbial dysbiosis and specific alterations of gut microbiota composition that occur during the early stages of glucose intolerance, is especially essential. This will allow for more personalised patient management through pharmacotherapy or dietary interventions. Hence, this systematic review was conducted to summarise the existing evidence related to microbiota composition and diversity in prediabetic (preDM) and newly diagnosed T2DM (newDM) individuals in comparison to individuals with normal glucose tolerance (nonDM). A systematic search of the PubMed, MEDLINE and CINAHL databases were conducted from inception to February 2021 supplemented with manual searches of the list of references. The primary keywords of “type 2 diabetes”, “prediabetes”, “newly-diagnosed” and “gut microbiota” were used. Observational studies that conducted analysis of the gut microbiota of respondents with preDM and newDM were included. The quality of the studies was assessed using the modified Newcastle-Ottawa scale by independent reviewers. A total of 18 studies (5,489 participants) were included. The preDM and newDM individuals exhibited low gut microbial diversity and increased abundance of phylum Firmicutes along with decreased abundance of Bacteroidetes. At the genus/ species levels, decreased abundance of Faecalibacterium prausnitzii, Roseburia, Dialister, Flavonifractor, Alistipes, Haemophilus and Akkermansia muciniphila and increased abundance of Lactobacillus, Streptococcus, Escherichia, Veillonella and Collinsella were more frequently observed in the disease groups than in the nonDM group. Lactobacillus was also found to positively correlate with FPG, HbA1c and HOMA-IR. As Lactobacillus is an important probiotic genus, there is a need for further investigations on the species/ strain-specific role of this bacteria in glucose regulation mechanism and T2DM disease progression. Differences in dietary intake caused significant variation in specific bacterial abundances. More studies are needed to establish more consistent associations, between clinical biomarkers or dietary intake and specific gut bacterial composition in prediabetes and early T2DM.